Cost per additional responder for ixekizumab and other FDA-approved biologics in moderate-to-severe plaque psoriasis. (2nd December 2017) - Al Sawah, Sarah; Foster, Shonda A.; Burge, Russel; Amato, David; Schacht, Alexander; Zhu, Baojin; Hartz, Susanne; Leonardi, Craig
Abstract: Background: Evidence of the cost-efficacy of ixekizumab for the treatment of moderate-to-severe plaque psoriasis (PsO) in the US is limited. Objective: To estimate the number needed to treat (NNT) and monthly cost of achieving one additional Psoriasis Area and Severity Index (PASI) 75, 90, and 100 responder for ixekizumab and other Food and Drug Administration (FDA)-approved biologics in PsO. Methods: A network meta-analysis estimated the probability of achieving PASI 75, 90, or 100 response during induction for each biologic. NNTs were calculated using response difference of each respective biologic vs placebo at the end of induction. Monthly costs per additional PASI responder were based on FDA-approved doses, wholesale acquisition costs, and induction NNTs. Results: Induction NNTs for ixekizumab 80 mg once every 2 weeks (Q2W) relative to placebo were consistently lower across all levels of clearance compared with the other biologics. Monthly cost per additional responder was lowest for ustekinumab 45 mg at PASI 75 and for secukinumab 300 mg and ixekizumab 80 mg Q2W at PASI 90. Ixekizumab 80 mg Q2W had the lowest cost for PASI 100. Conclusion: In this analysis, ixekizumab is the most cost-efficient biologic in the US when targeting complete resolution, as measured by PASI 100 in PsO.